Large-scale, adhesive-free and omnidirectional 3D nanocone anti-reflection films for high performance photovoltaics. (April 2019) - Tang, Lei; Tsui, Kwong-Hoi; Leung, Siu-Fung; Zhang, Qianpeng; Kam, Matthew; Wang, Hsin-Ping; He, Jr-Hau; Fan, Zhiyong
Abstract: An effective and low-cost front-side anti-reflection (AR) technique has long been sought to enhance the performance of highly efficient photovoltaic devices due to its capability of maximizing the light absorption in photovoltaic devices. In order to achieve high throughput fabrication of nanostructured flexible and anti-reflection films, large-scale, nano-engineered wafer molds were fabricated in this work. Additionally, to gain in-depth understanding of the optical and electrical performance enhancement with AR films on polycrystalline Si solar cells, both theoretical and experimental studies were performed. Intriguingly, the nanocone structures demonstrated an efficient light trapping effect which reduced the surface reflection of a solar cell by 17.7% and therefore enhanced the overall electric output power of photovoltaic devices by 6% at normal light incidence. Notably, the output power improvement is even more significant at a larger light incident angle which is practically meaningful for daily operation of solar panels. The application of the developed AR films is not only limited to crystalline Si solar cells explored here, but also compatible with any types of photovoltaic technology for performance enhancement.